Crianças, consumo e negociação de sentidos: modos de brincar, usos da TV e da internet - Michelan, Cristiane Simão (2011)
The dissertation aims to investigate the consumption way of children in their relation with cultural goods, including toys, games, television and internet. Two analytical axes guide the reflection: first, the reconstitution and position taken in relation to the debate about childhood and tensions between some trends that advocate its "disappearance" and others that seek to analyze the changes inherent in contemporary conditions. The second axis concerns the mediations undertaken by the family, friends, school and by their own conceptions of the world that allow children to elaborate and re-elaborate - negotiate senses and meanings related to what they consume, not necessarily in an identical way as that the hegemonic media portrays. Although the cultural industry, with its contents and means of strong appeal and power of seduction, suggests lifestyles, the child, when making choices, does so mediated by repertoires and values obtained from their socialization process. The concepts contained in the British and Latin Americans cultural studies were used as theoretical-methodological references, through which it becomes possible to investigate the cultural context and the family, such as instances of mediation in the child's relationship with the media, and the need to understand the culture as everyday practice. Some of the ways through which children, aged between six and ten, relate to cultural products and assign various meanings to them, were searched and analyzed as methodological protocol and field research